한우 친자확인 효과 검증에 관한 연구 - 선두원; 박문성; 최규명; 김현권; 강호찬; 이정규; 이승수; 문선정; 임현태; Du-Won Sun; Moon-Sung Park; Kyu-Myeong Choi; et al. (농업생명과학연구, 2021)
일반적으로 혈통 정보가 검증된 송아지의 경우 부모로부터 전달받은 유전능력을 통해 비육 후 출하 시에 우수한 도체 성적을 나타낼 확률이 상대적으로 높다고 알려져 있고, 이를 근거로 경매 시장에서 높은 가격대를 형성하고 있으나 이에 대한 과학적인 검증이 미비한 실정이다. 그러나 최근 친자확인 사업을 통해 과학적 검증을 위한 자료 수집이 가능한 상황이다. 따라서 본 연구는 2014년부터 2019년까지 경남 ‘ㄱ’지역 송아지를 대상으로 친자확인을 실시한 결과와 송아지의 경매 낙찰가 자료를 활용하여, 친자확인이 송아지 경매 낙찰가에 미치는 영향에 대해 분석하였다. 그 결과 2014년 친자 일치율이 64.6%였으나 6년간 지속적인 친자확인을 통해 2019년도에는 91.4%로 친자 일치율이 26.8% 상승하였음을 확인하였고, 이는 경남 ‘ㄱ’지역 농가의 혈통관리에 대한 인식이 높아진 결과로 한우의 자연적 개량이 이루어지는데 친자확인이 긍정적인 영향을 미쳤다고 판단된다. 또한 친자확인 일치 여부에 따른 송아지 경매 낙찰가의 경우 친자 일치된 송아지가 불일치된 송아지에 비해 경매 낙찰가가 약 34만원 높게 낙찰 되었고, 친자 일치된 송아지 내 성별에 따라 수송아지와 암송아지가 친자 불일치된 송아지 보다 각각 약 37만원, 22만원 높은 가격에 낙찰되었다. 따라서 본 연구와 추가적인 연구를 진행한다면 추후 농장별 계획 교배와 정확한 혈통관리를 통한 신뢰도를 높이는 것이 수익에 긍정적인 효과와 지역 단위로 지속적인 친자확인의 관리가 한우산업에 긍정적인 효과를 유발할 수 있다는 것으로 사료된다. In general, it is known that in the case of calf who pedigree has been verified, the probability of having excellent carcass performance through the genetic ability inherited from parents is relatively high. Calf verified through this have a high price in the market. But, scientific verification of verified pedigree and prices is insufficient. Therefore, this study analyzed the effect of the Parental Identification (PI) on calf price by using the results of the PI on calf in ‘A’ region on Gyeongnam from 2014 to 2019 and marker price. As a result, the PI rate in 2014 was 64.6%, but after 6 years of continuous PI, the PI rate increased by 26.8% to 91.4% in 2019. This is a result of the increased awareness of the pedigree management in the ‘A’ region of Gyeongnam farms, and it can be seen that the PI had a positive effect on the natural improvement of Hanwoo. Also, in the case of calf market price based on matched or not, which is the result of the PI, market price of the calf matched by the PI was about 340,000 KRW higher than the calf not matched. Market price of the bull and cow matched by the PI were about 370,000 KRW and 220,000 KRW higher than the calf not matched, respectively. It was confirmed that increasing reliability by verifying the planned breeding for each farms and the accurate pedigree management through the PI had a positive effect on the income. Furthermore, if continuous the PI is carried out on a regional basis, it is thought that accurate pedigree management will be achieved, which will have a positive effect on the Hanwoo industry.